2020
DOI: 10.1016/j.infsof.2020.106257
|View full text |Cite
|
Sign up to set email alerts
|

Time pressure in software engineering: A systematic review

Abstract: Large project overruns and overtime work have been reported in the software industry. Experiments and case studies have investigated the relationship between time pressure and software quality and productivity. Our search strategy examined 5,332 papers and identified 88 papers as having relevant contributions related to time pressure in a software engineering. Our review investigated definitions, metrics, and causes of time pressure. Also, we map the papers to process phases and approaches. Last, we summarize … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 106 publications
3
50
0
1
Order By: Relevance
“…However, it was realized that there are three studies (i.e., S1, S4 and S6 in the In the same way, only three studies (S2, S7 and S15 from Table 1); were including TP in SE. Not only in this study but Kuutila et al, [17] also found very limited TP studies in the SE domain during their latest systematic literature. Based on the selected studies, no one denies that TP is useful but very dangerous if it is not handled well.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…However, it was realized that there are three studies (i.e., S1, S4 and S6 in the In the same way, only three studies (S2, S7 and S15 from Table 1); were including TP in SE. Not only in this study but Kuutila et al, [17] also found very limited TP studies in the SE domain during their latest systematic literature. Based on the selected studies, no one denies that TP is useful but very dangerous if it is not handled well.…”
Section: Discussionsupporting
confidence: 46%
“…Yet, the results are still not improving software development. TP can produce some software process improvement [17]. For instance, Ibanez et al, [33] study results' show that medium level time pressure increase employees strengths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [2], there are three big factors that become the basis for software project failure. First factor is that project doesn't meet all the functionalities according to SRS.…”
Section: Background Studymentioning
confidence: 99%
“…At the other hand, software engineering methods have been combined with these approaches to increase the reliability of the generated security keys to resist the dominated attacks over numerous applications. One of these methods is the fault tolerance technique that is based on self-checking process to detect the happened faults [3][4][5][6][7][8]. The solution for the detected fault can be addressed throughout different ways depending on the utilized application.…”
Section: Introductionmentioning
confidence: 99%